Aplikasi Akad Musyarakah Mutanaqishah pada Produk Pembiayaan Mitraguna Online BSI Mobile - Sa’idaturrohmah, Nur; Afifah Nuroini, Dina; Sulis Setiyawati, Putri; Rohmatul Umah, Shoffi; Wasifaul Qolbi, Syahroini (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2025)
The aim of this research is to determine the application of the Musyarakah Mutanaqishah agreement to online partner financing via the BSI Mobile application. The research method used is a qualitative research method where this research is descriptive and tends to use analysis. The result of this research is online partner financing on the BSI Mobile application using the Musyarakah Mutanaqishah scheme where this contract is a collaboration between the customer and the bank and gradually the ownership portion of one party will be gradually purchased by the other party so that the ownership becomes one hundred percent.